Trust, Information Quality, and User Perceptions in Mobile Social Networks: Implications for Mobile Learning and Health Crisis Communication - Alemerien, Khalid (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The coronavirus COVID-19 outbreak has become a global crisis, where most nations are suffering from severe health and economic consequences. As known, the probability of infection is high, so it is important to understand the public perception of trust in sources of information, especially mobile social networks (MSNs). As a result, this information will assist in better informing public health messaging. In this study, we surveyed the users of MSNs to understand their perceptions regarding the utilization of MSNs as communication platforms during the COVID-19 outbreak. An online survey was utilized to collect the responses of 854 MSN users in mid-November 2024 using a questionnaire that we developed. The sample of participants was fairly similar to the general MSNs population in terms of gender, age, usage time, and education level. We found that 60% of the respondents mentioned that there is a lot of misleading, inaccurate, and anonymous information. The majority of the respondents stated that utilizing MSNs can be a helpful tool to promote and explain strict infection prevention policies proposed by the government to control the outbreak. Based on our findings, health professionals should lead the COVID-19 response to enhance trust in information sources. Consequently, it is crucial to emphasize and enhance the understanding and views of the use of MSNs during and following the crisis period.